Rationality of Wali Songo's Da'wa in the Spread of Islam in Nusantara: A Critique of Mystical Narratives: A Critique of Mystical Narratives - Ahmad Sukran; Sukiman Sukiman; Liza Jauharotul Munfarida Al Khurriyyah (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2026)
The dominance of mystical and mythological narratives in the public discourse surrounding the Wali Songo has created an epistemological bias that obscures their intellectual and strategic dimensions during the Islamization of the Nusantara. This phenomenon leads to “decontextualized spiritual personalization,” where these figures are more frequently understood through miracles rather than their actual contributions as social and educational architects. This study aims to deconstruct these mystical myths while reconstructing the rational foundations of the Wali Songo’s da'wah, which are rooted in knowledge, culture, and diplomacy. This research employs a qualitative-descriptive method with a comprehensive historical analysis approach, involving heuristics, source criticism, interpretation, and historiography of classical texts and modern academic literature. The results reveal that the Wali Songo’s success was rooted in systematic da'wah strategies, including: (1) the institutionalization of education via the pesantren model; (2) dialogic cultural acculturation; (3) political-economic diplomacy; and (4) inclusive social transformation. These findings assert that the Wali Songo were not merely sacred figures, but agents of intellectual transformation who established the groundwork for modern, critical, and moderate Islamic education in Indonesia.